Status Epilepticus in Patients with Brain Tumours - SÜNTER, GÜLİN; MİDİ, İPEK; AĞAN YILDIRIM, KADRİYE (KARE PUBL, 2018)
Objectives: Status epilepticus (SE) is a medical and neurological emergency with high morbidity and mortality. There are a variety of potential etiologies. The aim of this study was to evaluate the type of SE episode recorded in patients with brain tumors and to determine the effect of primary and metastatic brain tumors and SE type on response to treatment and mortality. Methods: An SE patient database was examined for individuals with brain tumors diagnosed clinically and electrophysiologically. Demographic features, SE subtype, response to treatment, and mortality rate were recorded. Results: There were 38 (14%) SE episodes in patients with intracranial tumors in the database. Convulsive SE (CSE) was the most common type, with 23 (60%) instances recorded. There was no statistically significant correlation between SE episodes and the intracranial tumor type (p=0.76). In all, 40% (n=15) remained refractory despite appropriate treatment. Six patients died in the hospital. No statistically significant relationship was found between refractoriness and mortality (p=0.737). Conclusion: The most common type of SE episode in patients with brain tumors was CSE. The higher mortality of patients with brain tumors and SE episodes may be a result of systemic complications that can accompany tumors. In addition, the changes in awareness of patients with brain tumors as they experience tumor progression or edema may be misdiagnosed, and if NCSE does not come to mind, the diagnosis is delayed, which can increase mortality.
Keywords: Brain tumors; mortality; status epilepticus; REFRACTORY STATUS EPILEPTICUS; RISK-FACTORS; EPILEPSY; METASTASES; PROGNOSIS